A reassessment of the Biblical glosses of Theodore and Hadrian’s Canterbury School - Vosper, Emma (2019)
In 1954, Bernhard Bischoff published an article that revolutionised scholarly attitudes towards the Canterbury School of Archbishop Theodore (c. 602–690) and Abbot Hadrian (c. 630x37–709). This school is described with the utmost respect by Bede (c. 672-735). Yet scholars knew little about its character until the re-discovery, by Bischoff, of a series of biblical glosses whose origins could be traced back to the School’s teaching activity. Bischoff (and later Michael Lapidge) viewed these glosses as evidence of Canterbury’s literalist approach to exegetical study and its focus on Greek rather than Latin patristic sources. In the sixty-four years since Bischoff published his article, scholars have been reluctant to challenge his initial conclusions. The present thesis will examine sections of the Canterbury glosses that have thus far evaded analysis to prove that Canterbury’s teaching style was far more nuanced than has previously been thought.